Description of Life Cycle Stages of Fish Parasite Cymothoa pulchrum (Isopoda: Cymothoidae), with DNA Barcode Linked to Morphological Details - Hiroki Fujita; Haruki Shinoda; Yuzumi Okumura (Fishes)
Cymothoidae (Crustacea: Isopoda) infest fish in marine, brackish, and freshwater environments. Cymothoa pulchrum Lanchester, 1902 is a cymothoid commonly found in the buccal cavity of mainly Tetraodontiformes fishes, distributed in the central and western Indo-Pacific region. This study describes the morphology of each life cycle stage of C. pulchrum: adult female, transitional, adult male, juvenile, and manca. In addition, we obtained DNA sequences linked to the morphological information of this species. We compared it with the sequences in the database using the neighbor-joining tree based on cytochrome c oxidase subunit I (COI) and 16S rRNA. Prior to this study, morphological data on the immature stages of Japanese Cymothoa was limited to juveniles of Cymothoa indica Schioedte and Meinert, 1884. The research identified 12 distinct morphological features that differentiate juvenile C. pulchrum from juvenile C. indica. Molecular analysis revealed that the COI sequences obtained in this study matched some of the C. pulchrum sequences in the database, whereas other sequences in the database formed a clade with Cymothoa eremita (Brünnich, 1783). In the phylogenetic tree based on 16S rRNA, C. pulchrum was also divided into two groups. In the COI phylogenetic tree, C. pulchrum and C. eremita form a total of five groups, and these two species might need to be re-examined taxonomically and molecularly.